Three Cups of Tea : One Man's Mission to Promote Peace, One School at a Time - Mortenson, Greg and Relin, David Oliver (Rawalpindi, Pakistan Army Publishing House, 2011)
One man's campaign to build schools in the most dangerous, remote, and anti-American reaches of Asia: in 1993 Greg Mortenson was an American mountain-climbing bum wandering emaciated and lost through Pakistan's Karakoram. After he was taken in and nursed back to health by the people of a Pakistani village, he promised to return one day and build them a school. From that rash, earnest promise grew one of the most incredible humanitarian campaigns of our time--Mortenson's one-man mission to counteract extremism by building schools, especially for girls, throughout the breeding ground of the Taliban. In a region where Americans are often feared and hated, he has survived kidnapping, death threats, and wrenching separations from his wife and children. But his success speaks for itself--at last count, his Central Asia Institute had built fifty-five schools.--From publisher description.
Include Map and index
Keywords: Afghanistan -- Pakistan -- Girls' schools -- Humanitarian assistance, American -- Mountaineers -- Mortenson, Greg